Management Of Acute Ankle Sprain: A Systematic Review - Kholis, Anja Hesnia; Hanum Hilfida, Nurullia; Lailiah, Novianti; Harista, Dessy Rindiyanti; Christianingsih, Siska; Septanto, Aby Nugrah (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: This paper aims to provide a literature review evaluating treatment strategies for acute ankle sprain. Methods: This article The method of search articles through electronic-based databases, Science Direct, Pubmed, and Web of Sciences. Articles collected have been for publication between 2014 - 2024 and selected based on quantitative research, and topic treatment of ankle sprain compatibility with keywords. The eligibility of the studies was assessed using the Joanna Briggs Institute (JBI) guidelines, and the PRISMA diagram was employed to organize the search results Results: A total of ten studies met the inclusion criteria, all of which had experimental designs. Various types of interventions were identified from the collected literature. A multidisciplinary approach that integrates manual techniques, physical therapy, medical care, and preventive education provides optimal results in the management of ankle injuries. Proper management treatment and rehabilitation to heal correctly and minimize the risk of re-injury Conclusion: Future research should define comprehensive treatment acute ankle sprain to enhance short and long term care and clinical outcomes in nursing context.